Effects Of Lower Limb Neurodynamic In Short Hamstring Syndrome - Antari, Ni Komang Ayu Juni; Kinandana, Gede Parta; Nugraha, Made Hendra Satria; Negara, Anak Agung Gede Angga Puspa (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Injury to the hamstring muscle is a very common site of injury in general sports or work-related physical activity. The purpose of this study was to compare the effectiveness of the addition of lower limb neurodynamics to the intervention of ultrasound therapy and stretching in short hamstring syndrome. Methods: This study is a Randomized Controlled Trial with a Pre-Test and Post-Test Group Design. The number of subjects in this study was 30 respondents, who were divided into 2 groups, namely the control group (n = 15) and the treatment group (n = 15). In the control group, subjects received a combination of ultrasound therapy and stretching. In the treatment group, subjects received a combination of ultrasound therapy, stretching, and lower limb neurodynamics. The intervention was carried out three times a week for four weeks (12 sessions). The length of the hamstring muscles is measured by straight leg raise (SLR) range of motion (ROM) and passive knee extension (PKE) ROM using a goniometer. Results: The results of statistical analysis showed that there was a significant difference between the two groups in the difference between the SLR ROM and PKE ROM before and after the intervention measured using a goniometer (p = 0.000). Conclusion: The addition of lower limb neurodynamics in the combination of ultrasound therapy and stretching intervention is proven to increase SLR ROM and PKE ROM in cases of the short hamstring. Lower limb neurodynamics could be used in clinical practice as an alternative to improving short hamstring syndrome.